2022
DOI: 10.1101/2022.04.08.487687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Improvement of Highly Protective Anti-Malarial Antibodies

Abstract: Antibody CIS43 binds Plasmodium falciparum circumsporozoite protein (PfCSP) and protects against malaria, as recently demonstrated clinically. To improve the efficacy of CIS43, we developed an in silico pipeline to optimize the interaction energy of CIS43 to its junctional epitope (peptide 21: PfCSP residues 101-115). Starting from two improved CIS43 variants, recently elicited from a CIS43-germline knock-in mice, single and double amino acid substitutions in the peptide 21-proximal heavy (VH) and light (VL) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recent efforts to enhance the protective efficacy of anti-PfCSP mAbs through phage display, inferred GL maturation, and in silico optimization have shown promise, showcasing the potential for antibody engineering to improve naturally acquired potent mAbs. 44 , 45 , 46 We isolated and characterized Ky224, which adopted a so far unreported binding mode and demonstrated liver burden inhibition comparable with the best 1210-like mAbs studied here despite exhibiting relatively low affinity for PfCSP and poor cross-reactivity to the major NANP repeat. In contrast to the 1210-like mAbs that bound the NPDP peptide with the NANP motif positioned between the N- and C-core, Ky224 induced an NPDP peptide configuration centered on the NVDP motif ( Figure 2 ), similar to neutralizing mAb L9.…”
Section: Discussionmentioning
confidence: 95%
“…Recent efforts to enhance the protective efficacy of anti-PfCSP mAbs through phage display, inferred GL maturation, and in silico optimization have shown promise, showcasing the potential for antibody engineering to improve naturally acquired potent mAbs. 44 , 45 , 46 We isolated and characterized Ky224, which adopted a so far unreported binding mode and demonstrated liver burden inhibition comparable with the best 1210-like mAbs studied here despite exhibiting relatively low affinity for PfCSP and poor cross-reactivity to the major NANP repeat. In contrast to the 1210-like mAbs that bound the NPDP peptide with the NANP motif positioned between the N- and C-core, Ky224 induced an NPDP peptide configuration centered on the NVDP motif ( Figure 2 ), similar to neutralizing mAb L9.…”
Section: Discussionmentioning
confidence: 95%
“…While experimental results showed that antibody-antigen binding affinity strongly correlated with in silico binding energies, suggesting that the model was successfully modeling the intended interaction, the correlation between binding affinity and protection was not universal. 74 Rawi's group is improving upon their in silico pipeline by devising ways to introduce mutations throughout the Fab region, not just around the antigen-binding site, and to select for mutations that improve other features, such as heavy-light chain interactions, solubility, half-life, and aggregation. As for P3-43, the group is moving forward with testing its ability to protect in a mosquito bite challenge and to assess its developability.…”
Section: In Silico Improvement Of An Antimalarial Antibodymentioning
confidence: 99%